Clinical impressions of anthrax from the 2006 outbreak in Saskatchewan - Himsworth, Chelsea G. (Canadian Veterinary Medical Association, 2009)
Clinical signs and carcass traits observed during the 2006 Saskatchewan anthrax outbreak were largely consistent with those previously published, except for cutaneous anthrax and anthrax mastitis in cows, and subcutaneous edema in bulls and horses. Failure of blood to clot was the most reliable indicator of anthrax in carcasses.